2D large beam inclination angle multibeam array antenna without beamforming network. Issue 6 (18th August 2019) - Dou, Haipeng; Ma, Runbo; Han, Liping; Han, Guorui; Yang, Rongcao; Zhang, Wenmei
ABSTRACT: A 2D multibeam array antenna without beamforming network is proposed in this paper. The antenna can radiate nine beams pointing to different directions in 2D space. By etching nine U-shaped slots on the ground plane, −10-dB impedance bandwidth is improved and beam inclination angles are enlarged. The measured results show that the antenna has a −10-dB impedance bandwidth of 7.5% (from 8.16 to 8.8 GHz). The inclination angles of the scanning beams are about ±36° (in the planes of φ = 0°, 45°, and −45°) and ±30° (in the plane of φ = 90°).